La responsabilidad social empresarial de las comercializadoras de combustible y su impacto económico en el cantón Quevedo periodo 2010-2014 - Mora Reinoso, Darwin Alexander (2015)
fuel comercializadoras referred to as " gas stations " are part of micro, small and medium enterprises (SMEs) , which are immersed in a level of competitiveness that requires constant analysis of internal and external factors inorder to establish strategies for Social esponsibility business to enable them to meet the needs and demands of the labor market and maintain customer loyalty influencing productivity and business profitability. Because of this, came the need for a business assessment to fuel service stations dedicated to the intermediary marketing this product for motor vehicles that are legally established and located in the city Quevedo. For this, I was raised as an objective "Identify practices of Social Responsibility fuel marketers and their economic impact in the canton Quevedo. Period 2010 -2014.In the first chapter the Contextual Framework for Research on the importance of Corporate Social Responsibility in fuel marketers Quevedo Canton analyzes is presented. The existing problem arises in implementing strategies that benefit the internal, external customers and the environment. The second chapter frames the theoretical foundation of Corporate Social Responsibility, scope, actions, norms and standards, benefits, items and influence on business in Latin America and Ecuador, as well as the socioenvironmental protection. The third chapter explains the methodological procedure used. In the fourth chapter the results is detailed and is done discussing them , in which it is reported that traders of fuel does not maintain a culture or manual CSR clearly structured so that its activities have not generated the total atisfaction in the quality of service provided to external customers and inefficient administrative policies for the benefit of the internal customer of the company.